Development of Islamic Religious Education Teacher Competency and Character Through Blended Learning - St Rohmatul Laili; Triyo Supriyatno; Abd. Gafur (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article aims to determine the development of IRE (Islamic Religious Education) teacher competence and character through hybrid learning at SMP N 2 Kedungpring. The research method uses a qualitative research type with a case study approach. The results of the study stated that: (1) the development of the competence of IRE teachers at SMP N 2 Kedungpring was carried out through increasing the branding personality of each educator with the support of school programs in the form of workshops, seminars, training, mentoring, training, and others, (2) competence The teacher's pedagogy is realized by mastering the material, optimal classroom management, understanding student characteristics, selecting media, methods, and learning strategies according to student needs, while the professional competence of teachers is shown through the background of educators who have met the qualifications of national standards, are competent in the field, trustworthy in carrying out their duties, and have an average teaching experience of more than 5 years, (3) the use of the hybrid learning method is shown through teacher preparation in improving competence, hybrid learning is used as a learning tool during a pandemic, through hybrid learning teacher competence in schools increases because of the series Participate in workshop forums, seminars, education and training, and so on.